The Analysis of Students’ Problems in Learning Speaking - Amelia, Resty; Husnayaini, ihda (Fakultas Tarbiyah, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
This study set out to determine the nature of the difficulties students have when learning to speak and the contributing variables to these difficulties. In this study, descriptive qualitative method was employed, and questionnaire as well as interview were used as the instruments. The sample of this study were 51 students of Islamic middle school in Puding Besar District, Bangka Belitung Province. The result of questionnaire was analyzed by means of average. It was found that the students had problems in speaking, especially linguistic and non-linguistic problems. In linguistic problems, they were in high criteria, and in non-linguistic problems they were medium. It means these problems had to be taken seriously. Therefore, the teacher should pay more attention to what the students need. In addition, it was also found that there were some factors causing the problems: they lacked self-confidence and had low motivation. Thus, the teacher should make the learning process more fun and interesting in order to make the students motivated.